Analisis Kepuasan Pasien Bersalin Terhadap Pelayanan Kebidanan Di Ruang VK RSUD Cimacan : Analysis of Satisfaction of Maternity Patients with Midwifery Services in the VK Room of Cimacan Hospital - Romdhana, Alice; Dewi, S.ST, M.Kes, Meinasari Kurnia (Indonesian Scholar Journal of Nursing and Midwifery Science, 2023)
Introduction: The results of the Community Satisfaction Survey at Cimacan Hospital in 2020 were 77,26. Meanwhile, the Community Satisfaction Survey Data for 2021 Cimacan Hospital obtained a value of 80,57; Observing the results of the survey there is an interesting thing, namely the average value of the Complaint handling element, meaning that even though the value of community satisfaction in handling complaints is the highest, there is an element of "Complaint" or things that are not in accordance with the wishes of the community/patients. The purpose of this study was to analyze the Satisfaction of Maternity Patients with Midwifery Services in the VK Room of Cimacan Hospital in 2022. Methods: This research is qualitative using 2 models, namely Conformity Level Analysis by comparing the importance score (Patient Satisfaction) with the performance score (Quality of Service) on the dimensions of Tangibles, Reliability, Responsiveness, Assurance, Empathy, and the Cartesian Diagram model with calculations using the Importance Performance Analysis Table. Results: Validity Test Results Level of performance/quality of service has R count 0,64> R table 0,227 declared valid. Patient Interest/Satisfaction Validity Test Results R count 0,567 > R table 0,227 declared valid. The results of the Reliability Test obtained Cronbach Alpha values ​​from the Level of Performance/Service Quality variable of 0,923 and the Level of Interest/Consumer Satisfaction variable of 0,863 > Cut of Value 0,60 so that it is declared reliable/consistent. The results of the analysis of the suitability level of the selected indicators are 96,08% (very suitable). The results of the Importance-Performance Analysis calculation for service quality: Quadrant A (Top Priority) has 3 attributes; Quadrant B (Maintain Achievement) has 8 attributes; Quadrant C (Low Priority) has 5 attributes; Quadrant D (Excessive) has 3 attributes and there is 1 attribute right on the line between Quadrant B (Maintain Achievement) and Quadrant D (Excessive). Discussion: There is 1 attribute right on the line between Quadrant B (Maintain Achievement) and Quadrant D (Excessive); namely the service is carried out according to schedule (Reliability). This attribute can be interpreted as some patients consider it less important and some others consider it very important. Meanwhile, the Cimacan Hospital has succeeded in carrying out this attribute excessively so that it is very satisfying for patients and must be maintained.